Menelisik Tafsir Modern-Kontemporer di Indonesia Abad 20 M - Hanna Salsabila; Farhan Muhammad; Ade Jamarudin; Muhamad Yoga Firdaus (Jurnal Dirosah Islamiyah, 2023)
The aim of this research is to explore contemporary contemporary modernist commentators in Indonesia. The method used in this research is qualitative through literature study using a historical approach. The results and discussion of this study include interpretation methodology, contemporary modern interpretation figures including; A. Hasan with his commentary work Al Furqan, Hasbi Ash Shiddieqy with his work Tafsir An-Nur, and Hamka with his work Tafsir Al-Azhar. This study concludes that there are A. Hasan, Hasbi Ash Shiddieqy and Hamka including contemporary modern commentators in Indonesia, whose style of interpretation is quite different from the interpretation in classical times. The presence of contemporary modern commentators in Indonesia adds to the scientific treasures of the Qur'an and Tafsir, especially in knowledge about contemporary modern interpreters. The weakness of this research is that it only describes three Indonesian mufassir figures in the contemporary modern age. This research recommends that we can study more deeply about the figures of interpretation in Indonesia in the modern and contemporary centuries.